Out of the blackout - Barnard, Robert (1984)
With the Nazis bombing London on a nightly basis, many families sent their children to the comparative safety of the countryside. When the Blitz ended, the families came for their kids, but no one ever came for Simon Thorn. His name appears on no evacuation list, and none of his belongings offer any clues to his origins. Now an adult, Simon is puzzled by an odd sense of familiarity when he walks down certain London streets. He remembers years of screaming nightmares that would terrify his bewildered foster parents. And he resolves to find out where he originally came from, even as everything he uncovers suggests that, really, he doesn't want to know.